Eksplorasi Kemampuan Berpikir Kritis dalam Menyelesaikan Soal Matematika Berbasis HOTS Ditinjau dari Gaya Belajar Siswa SD Negeri Gembira Desa Nangahale - Siti Romlah; Magdalena Dhema; Agustinus Angelaus Ete (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to determine the achievement of students‘ critical thinking skills in solving HOTS-based Mathematics problems in terms of students’ learning styles at SD Negeri Gembira, Nangahale Village. This type of descriptive qualitative research aims to present in-depth information about a subject. The research was conducted at SD Negeri Gembira Desa Nangahale in even semester on 10 April-17 May 2023. Primary data sources were obtained from observation. While secondary data sources were obtained from tests, questionnaires, and interviews. Data collection techniques using tests, learning style questionnaires and interviews. Data analysis in this study used miles and huberman model data analysis, namely data presentation, data reduction and conclusion drawing. The results showed that subjects with visual learning styles revealed that the thinking process on each indicator of critical thinking ability smoothly so that the subject could solve the problem correctly. Subjects with auditory learning styles reveal well the critical thinking process on each indicator of critical thinking ability.